The Impact of Holy Land Crusades on State Formation: War Mobilization, Trade Integration, and Political Development in Medieval Europe. (30th May 2016) - Blaydes, Lisa; Paik, Christopher
Abstract: Holy Land Crusades were among the most significant forms of military mobilization to occur during the medieval period. Crusader mobilization had important implications for European state formation. We find that areas with large numbers of Holy Land crusaders witnessed increased political stability and institutional development as well as greater urbanization associated with rising trade and capital accumulation, even after taking into account underlying levels of religiosity and economic development. Our findings contribute to a scholarly debate regarding when the essential elements of the modern state first began to appear. Although our causal mechanisms—which focus on the importance of war preparation and urban capital accumulation—resemble those emphasized by previous research, we date the point of critical transition to statehood centuries earlier, in line with scholars who emphasize the medieval origins of the modern state. We also point to one avenue by which the rise of Muslim military and political power may have affected European institutional development.